f(x) is a polynomial of degree 5 with leading coefficient 1 (coefficient of x^5). f(1)=1, f(2)=2, f(3)=3, f(4)=4, f(5)=5, Then find the value of f(6)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I want ask why i cant use this method by finding all constant of this x^5+ax^4+bx^3+cx^2+dx+e and then substitute 6 into the equation ?because the answer that it appears is 750 instead of 126
did the exact same! Well, except the fact that
g ( x ) = a ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 )
and then as it is monic, a can only be equal to 1.
Let the polynomial f(x) be equal to
(x-1)(x-2)(x-3)(x-4)(x-5) + x. Note that it satisfies all the given conditions i.e
f(1) = 1 f(2) = 2 f(3) = 3 f(4) = 4 And f(5) = 5
So putting the value of x as 6 in f(x) we get
5* 4* 3* 2* 1 + 6 = 126 So 126 is the answer...
Why should the polynomial equal the above given expression?
as given f(x)=x hence 1,2,3,4,5 are roots of f(x)-x=0 and equation can be written as f(x)-x=(x-1)(x-2)(X-3)(x-4)(x-5) thus for x=6 f(6)=6+(6-1)(6-2)(6-3)(6-4)(6-5) f(6)=126
Problem Loading...
Note Loading...
Set Loading...
Let g ( x ) = f ( x ) − x . Then g ( x ) = 0 for x = 1 , 2 , 3 , 4 , 5 .
Thus g ( x ) is a polynomial of degree 5 with a leading coefficient of 1 with roots x = 1 , 2 , 3 , 4 , 5 , and thus, by the Fundamental Theorem of Algebra, can be written
g ( x ) = ( x − 1 ) ( x − 2 ) ( x − 3 ) ( x − 4 ) ( x − 5 ) .
Plugging in x = 6 gives us that g ( 6 ) = 5 ∗ 4 ∗ 3 ∗ 2 ∗ 1 = 1 2 0 , and so
f ( 6 ) = g ( 6 ) + 6 = 1 2 6 .